Anti-carbonization coating, preparation method thereof and application of anti-carbonization coating in anti-carbonization construction method of multi-typhoon coastal sluice project

By applying a carbonization coating containing acrylic emulsion, 3-aminopropyltrimethoxysilane, calcium chloride and diethylenetriamine pentaacetic acid on the concrete surface of the sluice, a gel network was built, and the problem of carbonization of coastal sluices in the marine environment was solved, and effective anti-carbonization protection and structural stability were achieved.

CN119570323APending Publication Date: 2025-03-07SINOHYDRO ENG BUREAU 4
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411966131.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

Coastal sluices have long been subjected to chloride ion corrosion and carbonization in the marine environment, resulting in a decrease in concrete alkalinity and corrosion of steel bars, affecting structural stability and safety.

Method used

Using a carbonization-resistant coating, the raw material composition includes acrylic emulsion, 3-aminopropyltrimethoxysilane, calcium chloride and diethylenetriamine pentaacetic acid. The synergistic effect of these components is used to build a gel network, fill concrete pores, prevent carbon dioxide from penetration, and fix carbon dioxide through chemical reactions.

Benefits of technology

Effectively prevent carbonization problems in the sluice gate, improve the anti-carbonization ability of concrete, extend the service life of the structure, and enhance the hydrophobicity of the concrete surface, block the infiltration of moisture and harmful ions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention provides an anti-carbonization coating, a preparation method thereof and application of the anti-carbonization coating in an anti-carbonization construction method of multiple coastal sluice projects, and belongs to the technical field of concrete building anti-carbonization. The anti-carbonization coating is prepared from the following raw materials in parts by mass: 40 to 50 parts of acrylic emulsion, 5 to 10 parts of 3-aminopropyltrimethoxysilane, 1 to 3 parts of calcium chloride, 2 to 5 parts of diethylenetriamine pentaacetic acid, 1 to 2 parts of coalescing agent, 1.5 to 2 parts of flatting agent, 0.5 to 1 part of dispersing agent, 0.3 to 0.5 part of defoaming agent and 5 to 10 parts of pigment filler. According to the anti-carbonization coating provided by the invention, a gel system is constructed through the synergistic effect of the coating components, so that concrete pores can be filled, carbon dioxide is prevented from permeating into concrete, and the gel system can absorb carbon dioxide and is fixed in the gel system through chemical reaction; when the anti-carbonization coating is coated on the surface of the water gate, the carbonization problem of the water gate can be effectively prevented.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of anti-carbonization of concrete buildings, and in particular to an anti-carbonization coating and a preparation method thereof, as well as application of an anti-carbonization construction method in a coastal sluice project with frequent typhoons. Background Art

[0002] As an important water conservancy project facility, coastal sluices have long been subjected to erosion from the marine environment, including chloride ion erosion and carbonization. Carbonization refers to the CO 2 Gas penetrates into the concrete through the pores of hardened concrete, and reacts chemically with its alkaline substances (calcium hydroxide) to form carbonate (calcium carbonate) and water, which reduces the alkalinity of the concrete. When the carbonization depth reaches the surface of the steel bar, it will destroy the passivation film on the surface of the steel bar, making the steel bar prone to rust, affecting the stability and safety of the structure. Therefore, how to improve the anti-carbonization ability of the sluice has become a problem that needs to be solved in the construction industry. Summary of the invention

[0003] In order to solve the problems mentioned in the background technology, the present invention provides an anti-carbonization coating. A gel system is constructed through the synergistic effect of the coating components to fill the pores in the concrete and prevent carbon dioxide from penetrating into the concrete. The gel system can also absorb carbon dioxide and fix it in the gel system through chemical reactions. Applying the anti-carbonization coating on the surface of a sluice can effectively prevent carbonization problems in the sluice.

[0004] Specifically: A carbonization-proof coating comprises, by weight, 40-50 parts of acrylic emulsion, 5-10 parts of 3-aminopropyltrimethoxysilane, 1-3 parts of calcium chloride, 2-5 parts of diethylenetriaminepentaacetic acid, 1-2 parts of film-forming aid, 1.5-2 parts of leveling agent, 0.5-1 part of dispersant, 0.3-0.5 part of defoamer and 5-10 parts of pigments and fillers.

[0005] Furthermore, the acrylic emulsion is selected from one or more of pure acrylic emulsion, silicone acrylic emulsion, styrene acrylic emulsion, and acetate acrylic emulsion.

[0006] Furthermore, the solid content of the acrylic emulsion is 40%-50%.

[0007] Furthermore, the film-forming aid is selected from one or more of propylene glycol diacetate, propylene glycol methyl ether acetate, propylene glycol methyl ether, dipropylene glycol monomethyl ether, and dipropylene glycol monobutyl ether.

[0008] Furthermore, the leveling agent is selected from one or more of acrylate, urea-formaldehyde resin, styrene-butadiene rubber, and tetrasodium pyrophosphate.

[0009] Furthermore, the dispersant is selected from one or more of methyl amyl alcohol, polyacrylamide, fatty acid polyethylene glycol ester, and polyvinyl pyrrolidone.

[0010] Furthermore, the defoaming agent is mineral oil.

[0011] Furthermore, the pigment filler is titanium dioxide.

[0012] On the other hand, the present invention also provides a method for preparing the above-mentioned anti-carbonization coating, the steps of which include: Step 1: Add pigments and fillers to the acrylic emulsion, keep the speed at 300-500 rpm, stir for 10-15 minutes, mix thoroughly, then add 3-aminopropyltrimethoxysilane, calcium chloride and diethylenetriaminepentaacetic acid, film-forming aid, leveling agent, dispersant in sequence, and continue stirring for 15-20 minutes; Step 2: Reduce the speed to 100-200 rpm, add defoamer, and stir for 15-20 minutes; Step 3: Use a 100-200 mesh filter to remove large particle impurities and undispersed agglomerates to obtain an anti-carbonization coating.

[0013] On the other hand, the present invention also provides the application of the above-mentioned anti-carbonization coating in the anti-carbonization construction method of coastal sluice projects with multiple typhoons, specifically, applying the anti-carbonization coating on the construction surface to be protected to form a protective coating.

[0014] Compared with the prior art, the present invention has the following beneficial features: 1. The anti-carbonization coating of the present invention adds 3-aminopropyltrimethoxysilane, calcium chloride and diethylenetriaminepentaacetic acid to the coating system, and the synergistic effect of the three is used to construct a gel network, fill the pores in the concrete to prevent carbon dioxide from penetrating into the concrete, and play an anti-carbonization effect; specifically, in the water vapor-rich environment of the coastal sluice, the trimethoxysilane group in the 3-aminopropyltrimethoxysilane is prone to hydrolysis reaction in the water vapor-rich environment to generate silanol groups and methanol, and the silanol groups generated by the hydrolysis undergo condensation reaction to form siloxane bonds (Si-O-Si), thereby constructing the basic skeleton structure of the gel; the free calcium ions of the calcium chloride can form coordination bonds or ionic bonds with the silanol groups, thereby enhancing the crosslinking degree of the gel network and improving The stability and mechanical strength of the gel, at the same time, the carbon dioxide infiltrated from the outside will combine with the calcium ions on the gel network to form calcium carbonate attached to the gel network, preventing carbon dioxide from penetrating into the concrete; diethylenetriaminepentaacetic acid has multiple carboxyl groups and amino groups, which can coordinate with calcium ions. The complex formed by diethylenetriaminepentaacetic acid and calcium ions can further interact with 3-aminopropyltrimethoxysilane and its hydrolysis products to regulate the activity and distribution of calcium ions, thereby affecting the formation and structure of the gel network. The amino and carboxyl groups of diethylenetriaminepentaacetic acid can also undergo condensation reactions or hydrogen bonding with the silanol groups produced by the hydrolysis of 3-aminopropyltrimethoxysilane, further improving the cross-linking structure of the gel network and making the gel network more uniform and stable.

[0015] 2. The anti-carbonization coating of the present invention comprises a gel system composed of 3-aminopropyltrimethoxysilane, calcium chloride and diethylenetriaminepentaacetic acid. The silanol groups in the system condense with the hydroxyl groups in concrete, and a stable cross-linked network is formed at the interface between the coating and the concrete through chemical bonds. The coating can be firmly attached to the concrete surface and the capillary channels of the concrete, and the concrete surface is converted from hydrophilic to hydrophobic, thereby preventing moisture and harmful ions carried by the moisture from penetrating into the interior of the concrete. DETAILED DESCRIPTION

[0016] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0017] In order to facilitate those skilled in the art to implement the present invention, some of the reagents used in the embodiments and comparative examples are now described: Acrylic emulsion: pure acrylic emulsion, solid content 48±1%, BASF Acronal® 7051; 3-Aminopropyltrimethoxysilane: Shandong Yishun Chemical; Calcium chloride: Shandong Shangshan Chemical; Diethylenetriaminepentaacetic acid: Shandong Shangwei Chemical; Film-forming aid: propylene glycol diacetate, Shandong Jibei New Materials; Leveling agent: Tetrasodium pyrophosphate, Jinan Jiayang Chemical; Dispersant: polyacrylamide, Handan Tengze Chemical; Defoamer: non-ionic mineral oil alcohol ether, Beijing Qifei Technology; Pigments and fillers: Titanium dioxide, Shandong Tengze Chemical.

[0018] Example 1 An anti-carbonization coating, the preparation method of which comprises: S1. Weigh 40 parts of acrylic emulsion, 10 parts of 3-aminopropyltrimethoxysilane, 3 parts of calcium chloride, 5 parts of diethylenetriaminepentaacetic acid, 2 parts of film-forming aid, 2 parts of leveling agent, 1 part of dispersant, 0.5 parts of defoamer, and 10 parts of pigments and fillers according to mass ratio, and set aside; S2, adding pigments and fillers to the acrylic emulsion and stirring, maintaining the speed at 500 rpm, stirring for 15 minutes, fully mixing, then adding 3-aminopropyltrimethoxysilane, calcium chloride and diethylenetriaminepentaacetic acid, film-forming aid, leveling agent, and dispersant in sequence, and continuing stirring for 20 minutes; S3, reduce the speed to 200 rpm, add defoamer to the mixture in S2, stir for 20 min, stop stirring, and set aside; S4. Pass the rough coating obtained in S3 through a 200-mesh filter to remove large particle impurities and undispersed agglomerates to obtain an anti-carbonization coating.

[0019] Example 2 An anti-carbonization coating, the preparation method of which comprises: S1. Weigh 50 parts of acrylic emulsion, 5 parts of 3-aminopropyltrimethoxysilane, 1 part of calcium chloride, 2 parts of diethylenetriaminepentaacetic acid, 2 parts of film-forming aid, 2 parts of leveling agent, 1 part of dispersant, 0.5 parts of defoaming agent, and 10 parts of pigments and fillers according to the mass ratio, and set aside; S2, adding pigments and fillers to the acrylic emulsion and stirring, maintaining the speed at 500 rpm, stirring for 15 minutes, fully mixing, then adding 3-aminopropyltrimethoxysilane, calcium chloride and diethylenetriaminepentaacetic acid, film-forming aid, leveling agent, and dispersant in sequence, and continuing stirring for 20 minutes; S3, reduce the speed to 200 rpm, add defoamer to the mixture in S2, stir for 20 min, stop stirring, and set aside; S4. Pass the rough coating obtained in S3 through a 200-mesh filter to remove large particle impurities and undispersed agglomerates to obtain an anti-carbonization coating.

[0020] Example 3 An anti-carbonization coating, the preparation method of which comprises: S1. Weigh 50 parts of acrylic emulsion, 10 parts of 3-aminopropyltrimethoxysilane, 3 parts of calcium chloride, 5 parts of diethylenetriaminepentaacetic acid, 1 part of film-forming aid, 1.5 parts of leveling agent, 0.5 parts of dispersant, 0.3 parts of defoaming agent, and 5 parts of pigments and fillers according to mass ratio, and set aside; S2, adding pigments and fillers to the acrylic emulsion and stirring, maintaining the speed at 300 rpm, stirring for 10 minutes, and fully mixing, then adding 3-aminopropyltrimethoxysilane, calcium chloride and diethylenetriaminepentaacetic acid, film-forming aid, leveling agent, and dispersant in sequence, and continuing stirring for 15 minutes; S3, reduce the speed to 100 rpm, add defoamer to the mixture in S2, stir for 15 min, stop stirring, and set aside; S4. Pass the rough coating obtained in S3 through a 100-mesh filter to remove large particle impurities and undispersed agglomerates to obtain an anti-carbonization coating.

[0021] Example 4 An anti-carbonization coating, the preparation method of which comprises: S1. Weigh 50 parts of acrylic emulsion, 10 parts of 3-aminopropyltrimethoxysilane, 3 parts of calcium chloride, 5 parts of diethylenetriaminepentaacetic acid, 1.5 parts of film-forming aid, 2 parts of leveling agent, 0.8 parts of dispersant, 0.4 parts of defoamer, and 7 parts of pigments and fillers according to the mass ratio, and set aside; S2, adding pigments and fillers to the acrylic emulsion and stirring, maintaining the speed at 400 rpm, stirring for 13 minutes, fully mixing, then adding 3-aminopropyltrimethoxysilane, calcium chloride and diethylenetriaminepentaacetic acid, film-forming aid, leveling agent, and dispersant in sequence, and continuing stirring for 15 minutes; S3, reduce the speed to 150 rpm, add defoamer to the mixture in S2, stir for 20 min, stop stirring, and set aside; S4. Pass the rough coating obtained in S3 through a 100-mesh filter to remove large particle impurities and undispersed agglomerates to obtain an anti-carbonization coating.

[0022] Example 5 An anti-carbonization coating, the preparation method of which comprises: S1. Weigh 45 parts of acrylic emulsion, 8 parts of 3-aminopropyltrimethoxysilane, 2 parts of calcium chloride, 3 parts of diethylenetriaminepentaacetic acid, 2 parts of film-forming aid, 2 parts of leveling agent, 0.8 parts of dispersant, 0.5 parts of defoamer, and 6 parts of pigments and fillers according to mass ratio, and set aside; S2, adding pigments and fillers to the acrylic emulsion and stirring, maintaining the speed at 400 rpm, stirring for 10 minutes, fully mixing, then adding 3-aminopropyltrimethoxysilane, calcium chloride and diethylenetriaminepentaacetic acid, film-forming aid, leveling agent, and dispersant in sequence, and continuing stirring for 20 minutes; S3, reduce the speed to 150 rpm, add defoamer to the mixture in S2, stir for 20 min, stop stirring, and set aside; S4. Pass the rough coating obtained in S3 through a 150-mesh filter to remove large particle impurities and undispersed agglomerates to obtain an anti-carbonization coating.

[0023] Comparative Example 1 A coating, the preparation method of which comprises: S1. Weigh 40 parts of acrylic emulsion, 10 parts of 3-aminopropyltrimethoxysilane, 5 parts of diethylenetriaminepentaacetic acid, 2 parts of film-forming aid, 2 parts of leveling agent, 1 part of dispersant, 0.5 parts of defoamer, and 10 parts of pigments and fillers according to mass ratio, and set aside; S2, adding pigments and fillers to the acrylic emulsion and stirring, maintaining the speed at 500 rpm, stirring for 15 minutes, fully mixing, then adding 3-aminopropyltrimethoxysilane and diethylenetriaminepentaacetic acid, film-forming aid, leveling agent, and dispersant in sequence, and continuing stirring for 20 minutes; S3, reduce the speed to 200 rpm, add defoamer to the mixture in S2, stir for 20 min, stop stirring, and set aside; S4. Pass the rough coating obtained in S3 through a 200-mesh filter to remove large particle impurities and undispersed agglomerates to obtain coating.

[0024] Comparative Example 2 A coating, the preparation method of which comprises: S1. Weigh 40 parts of acrylic emulsion, 10 parts of 3-aminopropyltrimethoxysilane, 3 parts of calcium chloride, 2 parts of film-forming aid, 2 parts of leveling agent, 1 part of dispersant, 0.5 parts of defoamer, and 10 parts of pigments and fillers according to the mass ratio and set aside; S2, adding pigments and fillers to the acrylic emulsion and stirring, maintaining the speed at 500 rpm, stirring for 15 minutes, and fully mixing, then adding 3-aminopropyltrimethoxysilane, calcium chloride, film-forming aid, leveling agent, and dispersant in sequence, and continuing stirring for 20 minutes; S3, reduce the speed to 200 rpm, add defoamer to the mixture in S2, stir for 20 min, stop stirring, and set aside; S4. Pass the rough coating obtained in S3 through a 200-mesh filter to remove large particle impurities and undispersed agglomerates to obtain coating.

[0025] Comparative Example 3 A coating, the preparation method of which comprises: S1. Weigh 40 parts of acrylic emulsion, 3 parts of calcium chloride, 5 parts of diethylenetriaminepentaacetic acid, 2 parts of film-forming aid, 2 parts of leveling agent, 1 part of dispersant, 0.5 parts of defoamer, and 10 parts of pigments and fillers according to mass ratio and set aside; S2, adding pigments and fillers to the acrylic emulsion and stirring, maintaining the speed at 500 rpm, stirring for 15 minutes, fully mixing, then adding calcium chloride and diethylenetriamine pentaacetic acid, film-forming aid, leveling agent, and dispersant in sequence, and continuing stirring for 20 minutes; S3, reduce the speed to 200 rpm, add defoamer to the mixture in S2, stir for 20 min, stop stirring, and set aside; S4. Pass the rough coating obtained in S3 through a 200-mesh filter to remove large particle impurities and undispersed agglomerates to obtain coating.

[0026] Concrete test sample preparation: Step 1: According to the mass ratio, weigh 400 parts of cement, 500 parts of sand, 100 parts of fly ash, 1000 parts of gravel, and 500 parts of water, stir and mix evenly, and cast to prepare a 100mm×100mm×400mm concrete block.

[0027] Step 2, after curing the reserved concrete test block under standard conditions for 30 days, dry and dehumidify; cover the five surfaces of the prepared concrete block with paraffin wax, and reserve one surface; Step 3, design 9 experimental groups, one of which is a blank group, and the other 8 groups are coated with the coatings prepared in Examples 1-5 and Comparative Examples 1-3 on their reserved surfaces, and the coating thickness is controlled at 2 mm.

[0028] Coating performance test: (1) Anti-carbonization test: Referring to GT / B 50082, three areas of equal size, A, B, and C, were marked horizontally on the concrete block of each experimental group. The values ​​of the three areas were measured separately when testing the carbonization depth. (2) Adhesion test: refer to GB / T 5210.

[0029] The test results are shown in the following table

[0030] The above test values ​​show that the blank sample was not protected against carbonization and carbonization occurred. Compared with the blank sample, the samples of Examples 1-5 showed no signs of carbonization after 60 days of testing, which shows that the anti-carbonization coating of the present invention has an excellent anti-carbonization protection effect on concrete buildings.

[0031] The coating component of Comparative Example 1 lacked calcium chloride compared to Examples 1-5, and showed signs of carbonization within a period of 30 to 60 days.

[0032] The coating component of Comparative Example 2 lacks diethylenetriaminepentaacetic acid compared to Examples 1-5, and shows signs of carbonization. The carbonization depths of the three regions A, B, and C vary greatly, which may be due to the incomplete and uneven formation of the gel system, and the coating adhesion decreases.

[0033] The coating component of Comparative Example 3 lacks 3-aminopropyltrimethoxysilane compared to Examples 1-5, and shows obvious signs of carbonization.

[0034] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. An anti-carbonization coating, characterized in that: The raw material composition includes, by weight: 40-50 parts of acrylic emulsion, 5-10 parts of 3-aminopropyltrimethoxysilane, 1-3 parts of calcium chloride, 2-5 parts of diethylenetriaminepentaacetic acid, 1-2 parts of film-forming aid, 1.5-2 parts of leveling agent, 0.5-1 part of dispersant, 0.3-0.5 part of defoaming agent and 5-10 parts of pigments and fillers.

2. The anti-carbonization coating according to claim 1, characterized in that: The acrylic emulsion is selected from one or more of pure acrylic emulsion, silicone acrylic emulsion, styrene acrylic emulsion and acetate acrylic emulsion.

3. The anti-carbonization coating according to claim 1, characterized in that: The solid content of the acrylic emulsion is 40%-50%.

4. The anti-carbonization coating according to claim 1, characterized in that: The film-forming aid is selected from one or more of propylene glycol diacetate, propylene glycol methyl ether acetate, propylene glycol methyl ether, dipropylene glycol monomethyl ether, and dipropylene glycol monobutyl ether.

5. The anti-carbonization coating according to claim 1, characterized in that: The leveling agent is selected from one or more of acrylate, urea-formaldehyde resin, styrene-butadiene rubber, and tetrasodium pyrophosphate.

6. The anti-carbonization coating according to claim 1, characterized in that: The dispersant is selected from one or more of methyl amyl alcohol, polyacrylamide, fatty acid polyethylene glycol ester, and polyvinyl pyrrolidone.

7. The anti-carbonization coating according to claim 1, characterized in that: The defoaming agent is mineral oil.

8. The anti-carbonization coating according to claim 1, characterized in that: The pigment and filler is titanium dioxide.

9. A method for preparing the anti-carbonization coating according to any one of claims 1 to 8, characterized in that: The steps include: Step 1: Add pigments and fillers to the acrylic emulsion, keep the speed at 300-500 rpm, stir for 10-15 minutes, mix thoroughly, then add 3-aminopropyltrimethoxysilane, calcium chloride and diethylenetriaminepentaacetic acid, film-forming aid, leveling agent, dispersant in sequence, and continue stirring for 15-20 minutes; Step 2: Reduce the speed to 100-200 rpm, add defoamer, and stir for 15-20 minutes; Step 3: Use a 100-200 mesh filter to remove large particle impurities and undispersed agglomerates to obtain an anti-carbonization coating.

10. An application of the anti-carbonization coating as claimed in any one of claims 1 to 8 in the anti-carbonization construction method of a coastal sluice project with frequent typhoons, characterized in that: The anti-carbonization coating is applied to the construction surface to be protected to form a protective coating.

Citation Information

Patent Citations

  • Concrete protection paint and preparation method thereof

    CN102936443A

  • Environment-friendly nanoscale bottom infiltrated layer material used for protecting concrete surface and preparation method of environment-friendly nanoscale bottom infiltrated layer material

    CN103232267A

  • Water-based transparent concrete water-proof carbonization-preventing coating and preparation method thereof

    CN103333559A

  • Water proofing crack resistance paint

    CN108690434A

  • Water repellent based on inorganic silicate as well as preparation method and application thereof

    CN112266638A